Native subsatellite test range for ground support of validation and verification space systems remote sensing - Атрошенко, Л. М.; Борщева, Г. А.; Горобец, Н. Н.; Костриков, А. Л.; Пивовар, Е. А.; Сафронова, Л. П.; Ярмольчук, Е. Д. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 1970)
The program of create national system for ground support validation and verification of the home remote sensing space systems is proposed and substantiated. This system consists of four sites for the operation of any types of remote sensing space-based systems with any resolution. The location of sites is Kharkov region and Odessa region. The author’s test objects for remote sensing systems in radio, infrared and optical ranges are site's metrological equipment. The site’s infrastructure and measuring equipment provide ground support for home and foreign remote sensing systems and the production of materials to solve a wide range of thematic tasks.